Pseudolichus solutocurtus Dubinin, 1956 (Acarina, Pterolichoidea) and Harpyrhynchus sp (Acarina, Harpyrhynchidae Dubinin, 1957) species recorded for the first time on wild partridges in Turkey - Aksin, N; Erdogmus, Z (Tubitak Scientific & Technological Research Council Turkey, 2005)
This study was performed to determine the presence of mite species on wild partridges in Elazig district. For this purpose, a total of 68 partridges were caught in the 1996-2000 hunting seasons and inspected for the presence of mite species. At the end of the examinations 8 partridges were found to be infested by mites. Two different mite species were found on the infested 1 Dubinin, 1956) and Harpyrhynchus sp. (Harpyrhynchidae P the mite fauna of Turkey were found.
Keywords: acar; wild partridge; pterolichoidea; pseudolichus solutocurtus; harpyrhynchidea; harpyrhynchus sp; turkey